Влияние старения на циклическую стабильность в монокристаллах Ni44Fe19Ga27Co10 - Жердева, Мария Валериевна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The study of the effect of heat treatment on the cyclic stability of superelasticity was carried out on Ni44Fe19Ga27Co10 single crystals with the [001] orientation under compression (load/unload). It is shown that both quenched and aged Ni44Fe19Ga27Co10 single crystals have a high stability of superelasticity and withstand more than 105 load/unload cycles before destruction. The separation of the second phase particles in aged crystals led to a change in the mechanism of degradation of superelasticity. For quenched crystals, the dependence of the superelasticity parameters on the number of cycles consists of two stages. On the contrary, aged crystals are characterized by three stages in the dependence of the superelasticity parameters on the number of cycles.